PELATIHAN PEMBUATAN WEBSITE TOKO ONLINE DAN LANDING PAGE MENGGUNAKAN CANVA DI SMK TRITECH INDONESIA - Ommi Alfina; Elida Tuti Siregar; Aisyah Putri Angelina (Universitas Methodist Indonesia, 2022)
Community service is the Tri Dharma of Higher Education which has now become an obligation and is an agenda for routine activities every semester as a responsibility and thought to the community, especially the community in the field of education. When viewed also, the current curriculum sharpens students to think creatively, skillfully, independently, and to race on technology. To improve the performance of education in the future, information systems and information technology are needed, which not only function as a means of support, but as the main weapon to support the success of the world of education so that they can compete in the global world. One of them is the field of graphic design. If we think that image design can only be done by a graphic designer, now we can handle that freely using the Canva application, which is an online design program that provides various visual content such as websites, landing pages, presentations, resumes, posters, pamphlets, brochures, graphics, infographics, banners, bookmarks, bulletins, and so on. Through training for Tritech Indonesia Vocational School students, it is hoped that they can use the Canva application to create an online store website and its landing page correctly as a support in the teaching and learning process.